People with disabilities: Fighting for their rights in the USA and Brazil / Pessoas com deficiência: luta por seus direitos nos Estados Unidos e no Brasil - Angelucci, Carla Biancha; Block, Pamela Block; Santos, Larissa Costa dos (Revista de Educação PUC-Campinas, 2017)
This study focuses on guaranteeing of the right to Education for people with disabilities, from the point of view of the human rights organization and the Special Education policy in two countries: United States of America and Brazil. The goal was to understand how the right to Education has been guaranteed to people with disabilities in these two countries. Since the law in the United States of America is organized at state level, New York was chosen as example. We made a comparative study not to produce a ranking that shows what is the best or worst way of committing to implement the right to education for people with disabilities, but rather to understand, through different political, cultural and social contexts, the ways in which such rights were brought forth in the law and in public policy design. We present a brief history of disability rights in the United States of America and Brazil. Then the Special Education policy in both countries is discussed, and some comments are made on Special Education in the state of New York. There are differences related to the idea of inclusion as adopted by each country, because political and legal organization in both countries differ significantly, especially about the definition of the target audience and the definition of the educational tools to beused. Both countries emphasize the participation of disability rights social movements in the creation and monitoring of public policies. Keywords: People with disabilities. Social rights. Special Education.